2011
DOI: 10.1590/s0101-28002011000100003
|View full text |Cite
|
Sign up to set email alerts
|

Comparação da capacidade cognitiva de pacientes em programa de hemodiálise crônica entre os que realizam atividade física assistida e os inativos

Abstract: Physical inactivity is a determinant of clinical disorders and psychological problems in patients with chronic kidney disease. In two satellite clinics, a program of physical activity (PA) was offered to 86 patients undergoing hemodialysis. Of those, 49 patients entered the PA program spontaneously and 37 remained inactive. After six months, a satisfaction self-reported questionnaire and the Modified Mini-Mental State (3MS) Examination for assessment of cognitive function were applied. Cognition was compared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 4 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…The impact of exercise on cognitive function in patients with CKD remains uncertain, and there is a scarcity of published data in this area. In a small‐scale, nonrandomized study of a population of dialysis patients, exercise training was associated with better cognitive function (as judged by the Modified Mini‐Mental State Examination score) [81]. Similarly, a small pilot RCT in HD patients showed that intradialytic aerobic training three times per week for 4 months led to significant improvements in cognitive function and basilar blood flow velocity [82].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of exercise on cognitive function in patients with CKD remains uncertain, and there is a scarcity of published data in this area. In a small‐scale, nonrandomized study of a population of dialysis patients, exercise training was associated with better cognitive function (as judged by the Modified Mini‐Mental State Examination score) [81]. Similarly, a small pilot RCT in HD patients showed that intradialytic aerobic training three times per week for 4 months led to significant improvements in cognitive function and basilar blood flow velocity [82].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, physical inactivity constitutes one of the factors that determines clinical problems and mental disorders in renal patients. 10 Regarding leisure activities, a study that identified risk factors for loss of functional capacity among elderly people showed that leisure activities, monthly relationship with friends, watch TV and perform manual activities constituted in protective factors preventing loss functional for adequate control of non-communicable chronic diseases. The analysis of the research data was performed using descriptive statistics, SPSS statistical software and data presented in tables.…”
mentioning
confidence: 99%